Harmony Restoration Therapy in Management of Substance Induced Psychosis (A Case Study) - Sunday Obruche Erakpotobor (CV Projurnal Mitra Publikasi, 2025)
This paper reports a case study of Harmony Restoration Therapy in Management of a 28 year old male Patient with Substance induced psychosis. This Therapy developed by Ebigbo (1995) is an Africa-culture oriented therapy. It treats abnormal behaviour by restoring the equilibrium in human life and living using holistic as well as eclectic approaches. The theory of Harmony Restoration Therapy perceives man as a component of three entities, namely: Endo, Meso and Exo cosmos. There was a total of eight harmony restoration-based therapy sessions with emphases on psychoeducation, cognitive restructuring, family therapy and motivational interviews following referal of the Patient to the psychology unit. A six months follow-up revealed that Robinson has fully recovered without any episode of relapse. The study recommends that services of Clinical Psychologist should be employed in all clinical behaviours, especially when prognosis with pharmacotherapy is poor.